Social Network: JAZ Protein Interactions Expand Our Knowledge of Jasmonate Signaling - Browse, John; Wager, Amanda (Frontiers in Plant Science, 2012)
Members of the family of JASMONATE ZIM-DOMAIN (JAZ) proteins are key regulators of the jasmonate (JA) hormonal response. The 12-member family is characterized by three conserved domains, an N-terminal domain, a TIFY-containing ZINC-FINGER EXPRESSED IN INFLORESCENCE MERISTEM domain, and a C-terminal Jas domain. JAZ proteins regulate JA-responsive gene transcription by inhibiting DNA-binding transcription factors in the absence of JA. JAZ proteins interact in a hormone-dependent manner with CORONATINE INSENSITIVE 1 (COI1), the recognition component of the E3 ubiquitin ligase, SCFCOI1, resulting in the ubiquitination and subsequent degradation of JAZs via the 26S proteasome pathway. Since their discovery in 2007, JAZ proteins have been implicated in protein–protein interactions with multiple transcription factors. These studies have shed light on the mechanism by which JAZs repress transcription, are targeted for degradation, modulate the JA signaling response, and participate in crosstalk with other hormone signaling pathways. In this review, we will take a close look at the recent discoveries made possible by the characterization JAZ protein–protein interactions.